Effect of Pharmaceutical Effluents on Growth, Oxidative Defense, Secondary Metabolism, and Ion Homeostasis in Carrot - Iqbal Hussain; Kanwal Rehman; Muhammad Arslan Ashraf; Rizwan Rasheed; Javeria Gul; Muhammad Sajid Hamid Akash; Rohina Bashir (SAGE Publishing, 2021)
Pharmaceutical wastes are environmental micro pollutant and potential risk for the ecosystem. Therefore, the present study was planned to find out the effects of different pharmaceutical effluent (PE) regimes on growth, secondary metabolism, and oxidative defense in 2 carrot lines. The seeds of 2 carrot lines (DC-3 and T-29) were spread in plastic pots containing sandy loam soil. The design of experiment was completely randomized with 3 replicates per treatment. At vegetative stage, plants were irrigated with 5 different doses (control), 25%, 50%, 75% and 100%) of PE on every 3-day interval, while control plants were irrigated with canal water. The carrot roots were harvested after 25 days' application of the treatments to determine various attributes. High concentration of PE caused a substantial decline in growth, beta carotenoids, anthocyanin, total soluble protein, free amino acids, total soluble sugar, phenolic and flavonoid contents and an increase in proline, levels of H 2 O 2 and MDA, activities of antioxidant enzymes such as peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) in both lines. Moreover, PE caused significant reduction in the levels of essential nutrients (K + , Ca 2+ ) and increased in Na + content. However, T-29 line was found to be more PE tolerant because it had less H 2 O 2 , MDA and ascorbic acid contents. Thus, our findings showed that diluted PE (25%) could not be used for irrigation to increase the growth of plants in nutrients deprived environments without using bio filtration and biocarbon sorption technologies for treatments.